Assessment of TTX-s and TTX-r action potential conduction along neurites of NGF and GDNF cultured porcine DRG somata - Jonas, Robin; Klusch, Andreas; Schmelz, Martin; Petersen, Marlen; Carr, Richard (PLOS ONE, 2015)
Nine isoforms of voltage-gated sodium channels (NaV) have been characterized and in excitable tissues they are responsible for the initiation and conduction of action potentials. For primary afferent neurons residing in dorsal root ganglia (DRG), individual neurons may express multiple NaV isoforms extending the neuron’s functional capabilities. Since expression of NaV isoforms can be differentially regulated by neurotrophic factors we have examined the functional consequences of exposure to either nerve growth factor (NGF) or glial cell line-derived neurotrophic factor (GDNF) on action potential conduction in outgrowing cultured porcine neurites of DRG neurons. Calcium signals were recorded using the exogenous intensity based calcium indicator Fluo-8®, AM. In 94 neurons, calcium signals were conducted along neurites in response to electrical stimulation of the soma. At an image acquisition rate of 25 Hz it was possible to discern calcium transients in response to individual electrical stimuli. The peak amplitude of electrically-evoked calcium signals was limited by the ability of the neuron to follow the stimulus frequency. The stimulus frequency required to evoke a half-maximal calcium response was approximately 3 Hz at room temperature. In 13 of 14 (93%) NGF-responsive neurites, TTX-r NaV isoforms alone were sufficient to support propagated signals. In contrast, calcium signals mediated by TTX-r NaVs were evident in only 4 of 11 (36%) neurites from somata cultured in GDNF. This establishes a basis for assessing action potential signaling using calcium imaging techniques in individual cultured neurites and suggests that, in the pig, afferent nociceptor classes relying on the functional properties of TTX-r NaV isoforms, such as cold-nociceptors, most probably derive from NGF-responsive DRG neurons.